Species Diversity and Virulence Potential of the Beauveria bassiana Complex and Beauveria scarabaeidicola Complex - Wang, Yao; Fan, Qi; Wang, Dong; Zou, Wei-Qiu; Tang, De-Xiang; Hongthong, Preeyanat; Yu, Hong (Frontiers in Microbiology, 2022)
Beauveria is a very important fungal resource. Some Beauveria species have great economic and ecological value. Through surveying Beauveria in China and Thailand over the past four years, 15 Beauveria spp. were found and identified. Three new species—namely, B. polyrhachicola, B. songmingensis, and B. subscarabaeidicola—were described and illustrated based on morphological characteristics and molecular data. The phylogenetic positions of the 15 species were evaluated according to phylogenetic inferences based on six loci (nrSSU, nrLSU, TEF, RPB1, RPB2, and Bloc). Nine species of Beauveria in our study were isolated from adult scarab beetles (Coleoptera: Scarabaeidae). The pathogenicity of the isolates from the B. bassiana complex and B. scarabaeidicola complex was determined with three bioassays using B. mori and T. molitor larvae, in addition to Protaetia brevitarsis adults. The results indicated that the B. bassiana complex isolates had great potential in the biocontrol of the three insects; by contrast, the B. scarabaeidicola complex isolates showed obvious host specificity and low virulence.